Perlindungan Hukum Bagi Pegawai Honorer Setelah Berlakunya Undang-Undang Nomor 5 Tahun 2014 - Etwar Hukunala; Julista Mustamu; Revency Vania Rugebregt (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: this study discusses and analyzes the position and legal protection of temporary employees after the enactment of Law no. 5 Year 2014Purposes of the Research: To analyze and discuss legal arrangements regarding the position of honorary employees. And to analyze and discuss forms of legal protection for temporary employees.Methods of the Research: This research is a normative legal research. In this study, two approaches to the problem are used, namely the statutory approach and the conceptual approach. Sources of data obtained are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials is by collecting and grouping them according to their respective sections, both primary, secondary and tertiary laws. All data in this study were analyzed qualitatively.Results of the Research: The results of this study indicate that honorary employees are not included in the type of State Civil Apparatus (ASN). This is based on the provisions of Law Number 5 of 2014 concerning State Civil Apparatus. What is only mentioned in the ASN Law regarding types of employees are Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). With the enactment of Law Number 5 of 2014 greatly affects the position and legal protection of temporary employees. According to the Government Regulation, the term of service for honorary employees is up to 5 (five) years (from 2018 – 2023) and is given protection as applicable to PPPK in the form of health insurance, work accident insurance, and death insurance. Provisions regarding the provision of protection in the form of such guarantees for temporary employees still have to issue a Ministerial Regulation after receiving technical considerations from the minister who carries out government affairs in the financial sector.